Branding commodity, tourist & cultural products: some thoughts on applying semiotic analysis for the marketing strategy in each product category - Papadaki, Eirini (International Conference on Business and Economics - Hellenic Open University, 2023)
This paper proposes the adoption of semiotic analysis to the branding process in an attempt to understand the function of the specific sign system and successfully manage its designing and evaluation processes, from audience research to audience targeting. Specific case studies of commodity, tourist and cultural product branding will be presented, in an attempt to underline, in a parallel goal, the differences and similarities of the symbolic process involved in the three areas: commodities, tourism and culture. EL Classifications: M, Z Key words: branding, commodity products, cultural products, tourist products, semiotics